PENGARUH STRATEGI GREEN MARKETING DAN SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN KAOS LOKAL KERJODALU - Bougi Agustarinda Saka Pertiwi; Raya Sulistyowati (Jurnal Pendidikan Tata Niaga (JPTN), 2021)
A smart company will take advantage of environmental issues and technological advancements to attract more customers. The purpose of this study was to examine the effect of green marketing strategies and social media marketing on purchasing decisions on Kerjodalu t-shirts. This is a quantitative survey research that uses random sampling techniques to determine a sample of 131 customers. The data source used primary data in the form of online questionnaires with Likert scale measurement. The analytical test used is multiple linear analysis which includes the T test, F test and the coefficient of determination. The result of this research is that green marketing strategy has a significant effect on purchasing decisions t-count of 10.364. Social media marketing strategy has a significant effect on purchasing decisions with a t-count value of 2.026. Simultaneously, the green marketing strategy and social media marketing have an effect simultaneously with an F-count value of 108.469